2005
DOI: 10.1111/j.1365-2141.2005.05544.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, biologic features and outcome for young adult patients with acute lymphoblastic leukaemia

Abstract: SummaryYoung adult patients with acute lymphoblastic leukaemia (ALL) represent a unique epidemiologic subgroup in that therapy may be provided by either adult or paediatric oncologists. There seem to be no differences in presenting clinical features, immunophenotypic characteristics, or cytogenetic abnormalities for young adult ALL patients treated on paediatric or adult protocols with the exception of median age (16-paediatric trials versus 19-adult trials). There is no evidence to suggest that age within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
40
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 29 publications
(37 reference statements)
3
40
1
1
Order By: Relevance
“…The immunophenotyping of acute lymphoblastic leukemia by flow cytometry, based on the detection of surface and internal differentiation antigens, determines their cell type (B or T series) and differentiation stages to aid in diagnosis (6). The application of monoclonal antibodies provides more accurate immunophenotyping, improving the differential diagnosis of leukemia and lymphoma, as well as determining the source of malignant cells and their degree of differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The immunophenotyping of acute lymphoblastic leukemia by flow cytometry, based on the detection of surface and internal differentiation antigens, determines their cell type (B or T series) and differentiation stages to aid in diagnosis (6). The application of monoclonal antibodies provides more accurate immunophenotyping, improving the differential diagnosis of leukemia and lymphoma, as well as determining the source of malignant cells and their degree of differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Moreover, with increasing age through adolescence and adulthood, cure rates for ALL fall sharply, and the genetic and biological determinants of treatment failure remain incompletely understood. 8,9 ALL is characterized by recurring genetic alterations, including chromosomal aneuploidy (high hyperdiploidy and hypodiploidy), and a number of chromosomal rearrangements that dysregulate hematopoietic regulators, transcription factors and tyrosine kinases (for example, ETV6-RUNX1, TCF3-PBX1, BCR-ABL1, rearrangement of MLL and rearrangements of T-cell receptor genes to hematopoietic regulators and transcription factors in T-lineage ALL). 10,11 Although alterations associated with favorable outcome (for example, high hyperdiploidy and ETV6-RUNX1) are characteristic of childhood ALL, and the frequency of BCR-ABL1 (Philadelphia chromosome positive, or Ph þ ) ALL rises with age, 12 the differences in the frequencies of these recurring gross chromosomal rearrangements is insufficient to fully explain treatment failure in ALL, which occurs across the spectrum of cytogenetic subtypes, including cases that lack cytogenetic alterations.…”
mentioning
confidence: 99%
“…35,36 There are other factors that were historically believed to contribute to a worse outcome for the AYA population, including high rates of death during induction therapy. 18,37 However, more recent data have indicated that the induction …”
mentioning
confidence: 99%
“…6 The most substantial decreases in survival begin to become apparent at approximately 15 years of age. 18 Current chemotherapy protocols for children aged 1-10 years have led to a complete first remission rate of 98% and a 5-year event-free survival (EFS) rate of 80%-85%. 19 In contrast, the complete remission rate for adults is approximately 80%, with overall survival (OS) rates reported in the range of 35%-70%.…”
mentioning
confidence: 99%